2010
DOI: 10.1007/s11248-010-9404-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mycobacterium leprae HSP65 in tobacco and its effectiveness as an oral treatment in adjuvant-induced arthritis

Abstract: Transgenic plants are able to express molecules with antigenic properties. In recent years, this has led the pharmaceutical industry to use plants as alternative systems for the production of recombinant proteins. Plant-produced recominant proteins can have important applications in therapeutics, such as in the treatment of rheumatoid arthritis (RA). In this study, the mycobacterial HSP65 protein expressed in tobacco plants was found to be effective as a treatment for adjuvant-induced arthritis (AIA). We clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
2
0
1
Order By: Relevance
“…Again, the empty plasmid prompted a similar but less pronounced effect. This protective effect of hsp65 in distinct inflammatory conditions is highly supported by findings of many other authors [5861]. …”
Section: Discussionsupporting
confidence: 83%
“…Again, the empty plasmid prompted a similar but less pronounced effect. This protective effect of hsp65 in distinct inflammatory conditions is highly supported by findings of many other authors [5861]. …”
Section: Discussionsupporting
confidence: 83%
“…To confirm our results, we also tested an acute model of arthritis induced by methylated bovine serum albumin (mBSA) (35). Although there are several pieces of evidence on the tolerogenic role of Hsp65 in different arthritis models, including ingestion of recombinant Mycobacterium Hsp65 (36,37), the use of recombinant L. lactis has advantages: it has anti-inflammatory properties of its own, it survives through the digestive tract and delivers large amounts of Hsp65 directly into the mucosa, boosting its tolerogenic effect (30). In addition, L. lactis is a gram-positive lactic bacterium that produces an endotoxin free version of HSP65.…”
Section: Introductionmentioning
confidence: 55%
“…Likewise, the DNAhsp65 vaccine has also been evaluated for its ability to induce other autoimmune diseases, such as arthritis and encephalomyelitis to determine whether it has therapeutic properties in combating these diseases. Previously, the work by Rodríguez-Narciso et al (68) showed a recovery of body weight and reduced inflammation in the joints after oral administration of recombinant HSP65 protein produced in tobacco in rat adjuvant-induced arthritis. Corroborating this data, other works found that the administration of the DNAhsp65 vaccine did not induce arthritis (69) or encephalomyelitis in animal models, even when using the BCG/DNAhsp65 prime-boost approach (70).…”
Section: Dnahsp65 In Autoimmune Diseases Modulationmentioning
confidence: 99%